THE PERFORMANCE OF QUAILS 1 - 5 WEEKS AGE GIVEN DRAGON FRUIT PEEL JUICE THROUGH DRINKING WATER - L. E., Nova; Dewi, G. A. M. K.; Wirapartha, M.; Wirapartha, M. (Jurnal Peternakan Tropika, 2021)
This research was conducted to determine the performance of quails aged 1 - 5 weeks which were given dragon fruit peel juice through drinking water.  The experimental design used was a completely randomized design (CRD) consisting of 4 treatments and 4 replications, each of which consisted of 5 quails.  This study used 80 quails of Cotunix coturnix japonica which were 1 week old.  The treatments given were: drinking water without dragon fruit peel juice (P0), drinking water with 1% dragon fruit peel juice (P1), drinking water with 2% dragon fruit peel juice (P2), drinking water with 3% dragon fruit peel juice (P3).  The variables observed included initial body weight, ration consumption, drinking water consumption, body weight gain, final body weight and FCR.  The results showed that each variable of initial weight, ration consumption, drinking water consumption, body weight gain, final body weight and FCR treatment 0%, 1%, 2% and 3% were not significantly different (P>0.05).  Based on the results of the study it can be concluded that the provision of dragon fruit peel juice 1%, 2% and 3% through drinking water does not affect ration consumption, drinking water consumption, body weight gain, final body weight and FCR in Coturnix coturnix japonica quails aged 1-5 weeks. Key words: performance, quails, dragon fruit peel